2017
DOI: 10.1155/2017/8365685
|View full text |Cite
|
Sign up to set email alerts
|

On Consistency of Cross-Approximate Entropy in Cardiovascular and Artificial Environments

Abstract: Cross-approximate entropy (XApEn) quantifies the mutual orderliness of simultaneously recorded time series. Despite being derived from the firmly established solitary entropies, it has never reached their reputation and deployment. The aim of this study is to identify the problems that preclude wider XApEn implementation and to develop a set of solutions. Exact expressions for XApEn and its constitutive parts are derived and compared to values estimated from artificial data. This comparison revealed vast regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…For this reason, the probability zero is omitted and the averaging performed without the omitted probability. Different ways of correction exist, systematized in [10], but the comparison to the theoretical (and therefore correct) values in artificial signals with known distributions has shown that this simple correction outperforms the more complex ones.…”
Section: Entropy Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the probability zero is omitted and the averaging performed without the omitted probability. Different ways of correction exist, systematized in [10], but the comparison to the theoretical (and therefore correct) values in artificial signals with known distributions has shown that this simple correction outperforms the more complex ones.…”
Section: Entropy Methodsmentioning
confidence: 99%
“…In addition to the method for the quantification of baroreflex sensitivity [4,5], classical contributions rely on power spectrum density approach, as well as on multivariate autoregressive analysis [6]. More recent analyses implement tools designed specifically to assess the mutual orderliness of simultaneously recorded time series and the level of their (a)synchrony, such as cross-entropy [7,8] and its variations such as [9], [10], [3], including the multi-scale cross-entropy [11,12,13,14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most implemented types of entropy estimates used for measuring the similarity and self-similarity of biomedical data are Approximate entropy (ApEn) and Sample entropy (SampEn). Approximate entropy was introduced in [19] and well explained in [20,21]. It initiated many variations (FuzzyEn, BinEn) [22,23] but the SampEn [24] is the method that, considering its quotation rate [25], almost equals its predecessor ApEn.…”
mentioning
confidence: 99%
“…Finding the threshold level appropriate for the observed time series is a critical issue which has been elaborated in numerous contributions [27]- [29]. For this paper we used the method for cross-entropy proposed in [20].…”
mentioning
confidence: 99%